Shared Genetic Basis of Epilepsy and Behavior Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers from Columbia University, New York; UCLA; Northern Illinois University, DeKalb, IL; and Northwestern Children's Memorial Hospital, Chicago have examined whether the first-degree family history of unprovoked seizures in 308 probands with childhood onset epilepsy is associated with behavioral disorders.